Transformasi Pembukuan Digital Gratis Berbasis Microsoft Excel pada Warkop Motekar - Sari, Nova Permata (Yayasan Sagita Akademia Maju, 2026)
Micro and small enterprises played a crucial role in sustaining domestic economic stability; however, many businesses still relied on manual financial recording practices that limited accuracy and decision making. Warkop Motekar, a micro-scale coffee shop, experienced similar challenges due to the absence of structured digital bookkeeping and concerns regarding subscription-based accounting software costs. This community service project aimed to transform manual bookkeeping into a digital financial management system using Microsoft Excel as a free and accessible tool. The program was conducted from January to February 2026 through three stages: preparation, implementation, and evaluation. A customized Excel-based system named “Motekar Digital Finance” was designed and applied through one-on-one coaching sessions. The system integrated general journal entries, ledger, trial balance, income statement, and statement of financial position with automated formulas. The implementation results showed improved recording consistency, clear separation between cost of goods sold and operating expenses, and the generation of accurate financial statements. In January 2026, the business recorded a net profit and demonstrated a healthy financial position without liabilities. The evaluation stage indicated stable system usage and enhanced financial literacy. The transformation strengthened pricing accuracy, liquidity control, reinvestment planning, and overall business credibility, thereby increasing the enterprise’s sustainability and readiness for formal financing access.